Ambiente psicossocial de trabalho e marcadores de saúde mental em funcionários públicos - Lígia Amaral Muritiba dos Santos (2022)
SANTOS dos, L. A. M. Psychosocial work environment and mental health markers in civil servants. Dissertation (Masters in Nursing) - Escola de Enfermagem, Universidade Federal de Minas Gerais, Belo Horizonte, 2022. OBJECTIVE: To evaluate the association between the psychosocial work environment and mental health markers of civil servants in the first instance of the Minas Gerais judiciary, analyzing the existence of gender differences in the evaluated associations. METHOD: This is a cross-sectional study whose sample consisted of 1537 servants of the Minas Gerais judiciary. Sampling was stratified with simple random selection in the strata: gender, type of district; current position; age groups. The outcomes were psychotropic medication use and sleep problems, and the exposure variable was the psychosocial work environment. Sociodemographic, work, violence, health and lifestyle characteristics were considered as adjustment variables. The analyzed data come from the JUSTICEL study, 2016, Minas Gerais. The estimation of the prevalence ratio (with the respective 95% CI) was performed using the Poisson regression method with robust variance. RESULTS: The prevalence of psychotropic medication use was 21.5% and 10.7% in females and males, respectively. The prevalence of sleep problems was 32.8% for females and 28.7% for males. For females, they were associated with a lower prevalence of reports of psychotropic drugs prescribed by a doctor who was a judicial officer and performed sufficient physical activity during leisure time. Having high blood pressure and being bullied at work increased the likelihood of using these medications among women. As for sleep problems, for the female gender, it was associated with high-demand work, performing physical activities during leisure time, being single, having suffered bullying at work or physical violence. For the male gender, active and high demand work increased the consumption of psychotropic drugs. Regarding sleep problems, among men, physical activity, working at the TJMG for more than 20 years, having hypertension and suffering verbal violence in the work environment were association variables, the first being protection. CONCLUSION: An association was identified between the characteristics of the psychosocial work environment and the mental health of the servers, as favoring mental illness, especially in the aspects of working overtime, violence at work, especially psychological violence, and time of professional practice over 20 years worked. They also point out that high-demand and active work is negative for both genders, increasing the probability of mental illness. It was observed that women are more affected in their mental health than men. Another difference between genders is the higher occurrence of insomnia among women and higher consumption of psychotropic drugs among men. In this way, the adjustment of work environments, improving job satisfaction and reducing work stressors, can contribute to the prevention of mental health problems among civil servants.